Characterization of Chitosan from the Haliling Snail (Filopaludina javanica) Shell in South Kalimantan - Siska Musiam; Noor Aisyah (CHEMICA: Jurnal Teknik Kimia, 2020)
Chitosan is a renewable natural polymer derived from chitin which can be found in many invertebrate animals. Chitosan has non-toxic properties, is easily broken down (biodegradable and bioresorbable), and is able to adapt to its environment (biocompatibility). This study aims to characterize chitosan produced from haliling (Filopaludina javanica) shell waste originating from South Kalimantan. Haliling meat is consumed as a side dish by the people of South Kalimantan so that the shell becomes a waste that can be used as raw material for chitosan. Chitosan characterization included determination of yield, solubility test, calculation of the degree of deacetylation with Fourier Transform Infra Red (FTIR), as well as observing the crystallinity and morphology of the yield compounds by X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). The yield of chitosan obtained was 8.890% with the best solubility at 0.1 N HNO3 N. The FTIR analysis of chitosan obtained a degree of deacetylation of 60.581%. XRD and SEM data showed a crystallinity index of 52.945% with a granular surface.